Variable Surface Glycoprotein RoTat 1.2 PCR as a specific diagnostic tool for the detection of Trypanosoma evansi infections - Claes, Filip; Radwanska, Magda; Urakawa, Toyo; Majiwa, Phelix A.O.; Goddeeris, Bruno M.; Büscher, Philippe (Springer, 2004)
Based on the recently sequenced gene coding for the Trypanosoma evansi (T. evansi) RoTat 1.2 Variable Surface Glycoprotein (VSG), a primer pair was designed targeting the DNA region lacking homology to other known VSG genes. A total of 39 different trypanosome stocks were tested using the RoTat 1.2 based Polymerase Chain Reaction (PCR).This PCR yielded a 205 bp product in all T. evansi and in seven out of nine T. equiperdum strains tested. This product was not detected in the DNA from T. b. brucei, T. b. gambiense, T. b. rhodesiense, T. congolense, T. vivax and T. theileri parasites. The Rotat 1.2 PCR detects as few as 10 trypanosomes per reaction with purified DNA from blood samples, i.e. 50 trypanosomes/ml.PCR amplification of the RoTat 1.2 VSG gene is a specific marker for T. evansi strains, except T. evansi type B, and is especially useful in dyskinetoplastic strains where kDNA based markers may fail to amplify. Furthermore, our data support previous suggestions that some T. evansi stocks have been previously misclassified as T. equiperdum.